(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In the present paper, we first give four post-quantum integrals for functions of two variables, denoted by _acT_p,q, ^d_ aT_p,q, ^b_cT_p,q and ^bdT_p,q. Afterwards, each of these newly defined integrals is illustrated. Moreover, some new Hermite-Hadamard inequalities are established based on these definitions. We also show the correctness of these inequalities with the aid of some numerical examples.